Semantic and structural analysis of lexis denoting color in Russian language - Marta Nowaczyk (Kazimierz Wielki University, 2017)
The article determines an analysis of the lexis, used to express color in Russian. To achieve this aim, the theoretical aspect as well as the collected files of the selected linguistic units serving as the research material were presented. The examples relate to all the meanings of ten colors: red, orange, yellow, green, light blue, dark blue, purple, pink, brown, and scarlet.